Introduction to Evacuation Routes for Tsunami Earthquake Disaster Threats at SMKN 1 Meureubo: Sosialisasi Pengenalan Jalur Evakuasi Terhadap Ancaman Bencana Gempa Tsunami di SMKN 1 Meureubo - Cut Liliiza Yusra; Hilma Erliana; Kusmira Agustian; Santi Septiana Zarita; Luthfi; Andi Mustari; Rahmad Nuthihar; Chaira; Yunita Arafah; Keumala Fadhiela ND (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
This community service aims to identify and enhance the awareness and understanding of students at SMKN 1 Meureubo regarding evacuation routes in the face of earthquake and tsunami threats. Meureubo, located on the west coast of Aceh, is in a high-risk zone for tsunamis, making comprehension of evacuation routes crucial to minimizing the risk of casualties. This outreach involves participatory methods including counseling, evacuation drills, questionnaire distribution, and the dissemination of educational materials on the steps to be taken during a disaster. The evacuation routes introduced consist of five routes. The results of this activity show a significant increase in students' knowledge and preparedness for emergency evacuation procedures. Regarding the ease of access to the provided evacuation routes, 44.4% of respondents agreed, while 48.5% disagreed due to the lack of evacuation signs leading to the designated assembly points. Therefore, it is hoped that this activity will continue and be disseminated to the entire community of West Aceh Regency, especially in Meureubo sub-district, so that it can serve as a model to be implemented in other schools in disaster-prone areas to enhance the safety and well-being of the community.